Administration of anticoagulation strategies for portal vein thrombosis in cirrhosis: network meta-analysis - Li, Hui-Jun; Yin, Fu-Qiang; Ma, Yu-Tong; Gao, Teng-Yu; Tao, Yu-Ting; Liu, Xin; Shen, Xian-Feng; Zhang, Chao (Frontiers in Pharmacology, 2025)
ObjectivesEvidences for anticoagulation strategies in cirrhotic with portal vein thrombosis (PVT) are still insufficient. This study aims to comprehensively compare the therapeutic effects of different therapeutic therapeutic measures in individuals suffering from cirrhosis with PVT, with the ultimate goal of providing evidence-based recommendations for thrombolytic therapy in this population.MethodsStarting from 20 October 2023, a comprehensive search about therapeutic strategies for portal vein thrombosis in cirrhosis was conducted on PubMed, EMBASE, and Cochrane Library.Results19 studies were eventually incorporated into this study. Comparison with control in network meta-analysis, direct oral anticoagulants (DOACs) (RR = 2.15, 95%CI: 1.33, 3.48), LMWH (RR = 1.41, 95%CI: 1.01, 1.99), TIPS (RR = 5.68, 95%CI: 2.63, 12.24), warfarin (RR = 2.16, 95%CI: 1.46, 3.21), EBL plus propranolol (RR = 2.80, 95%CI: 1.18, 6.60), LMWH-DOACs sequential (RR = 7.92, 95%CI: 2.85, 21.99) and LMWH-warfarin sequential (RR = 2.26, 95%CI: 1.16, 4.42) significantly improved the incidence of complete recanalization. The anticoagulation drugs were ranked based on their SUCRA values, with the LMWH-DOACs sequential (92.7%), TIPS plus warfarin (91.3%), and TIPS (80.3%) emerging as the top three effective treatments.ConclusionIn this study, active anticoagulants were recommended for cirrhosis with PVT. The TIPS plus warfarin, LMWH-DOACs sequential, and TIPS improved the complete recanalization rate most effectively, and the EBL plus propranolol, heparin plus DOACs plus warfarin, and DOACs were highly recommended for increasing the incidence of partial recanalization. Warfarin and TIPS were recommended for reducing the frequency of bleeding events, while LMWH plus warfarin and DOACs proved to be most effective in decreasing the rate of major bleeding events. Warfarin, heparin plus DOACs plus warfarin, and DOACs demonstrated the most significant reduction in mortality rates, highlighting its potential as an effective intervention. TIPS plus warfarin, LMWH-DOACs sequential, and TIPS were recommended for reducing the occurrence of PVT expansion. Heparin plus DOACs plus warfarin was recommended for reducing the occurrence of hepatic encephalopathy, and protocols that involve TIPS were generally associated with a higher risk of hepatic encephalopathy. However, a longer follow-up period is necessary to comprehensively evaluate the efficacy of active anticoagulants therapy in patients with PVT in cirrhosis.